2023
DOI: 10.5194/egusphere-egu23-2956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Seasonal Streamflow Forecasts over South American Large Rivers

Abstract: <p>Society’s increasing demand for water and the need for its long-term management have motivated efforts toward improving seasonal streamflow forecasts. Currently, seasonal climate forecasts are routinely issued in meteorological centers around the world, generating information for decision-making and seasonal streamflow forecasting (SSF) studies that are becoming more frequent. Seasonal streamflow forecast skill derives from land surface initial conditions and atmospheric boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The predictive streamflow skill in the studied region decreases with the increase in lead times. Similar results have been reported to other hydrological studies (Greuell and Hutjes, 2022;Lucatero et al, 2018;Petry et al, 2021). The research in other areas, such as Denmark, showed limited streamflow skill beyond a one month lead time (Lucatero et al, 2018) and the same in South America where the peak streamflow could be predicted one month in advance (Petry et al, 2021).…”
Section: Performance Of the Seas Forecasting Skillsupporting
confidence: 89%
See 1 more Smart Citation
“…The predictive streamflow skill in the studied region decreases with the increase in lead times. Similar results have been reported to other hydrological studies (Greuell and Hutjes, 2022;Lucatero et al, 2018;Petry et al, 2021). The research in other areas, such as Denmark, showed limited streamflow skill beyond a one month lead time (Lucatero et al, 2018) and the same in South America where the peak streamflow could be predicted one month in advance (Petry et al, 2021).…”
Section: Performance Of the Seas Forecasting Skillsupporting
confidence: 89%
“…Similar results have been reported to other hydrological studies (Greuell and Hutjes, 2022;Lucatero et al, 2018;Petry et al, 2021). The research in other areas, such as Denmark, showed limited streamflow skill beyond a one month lead time (Lucatero et al, 2018) and the same in South America where the peak streamflow could be predicted one month in advance (Petry et al, 2021). The streamflow generation processes mainly come from the precipitation (Schmitt Quedi and Mainardi Fan, 2020), the streamflow skill hence presents similar patterns to the precipitation skill although at slightly lower levels.…”
Section: Performance Of the Seas Forecasting Skillsupporting
confidence: 88%